Borrelia carolinensis sp. nov., a new (14th) member of the Borrelia burgdorferi Sensu Lato complex from the southeastern region of the United States - Rudenko, Nataliia; Golovchenko, Maryna; Grubhoffer, Libor; Oliver, James H (Journal of clinical microbiology, 2009)
Approximately 118 Borrelia isolates were cultured from a variety of rodents, birds, and ticks collected in the southern United States. In addition to a highly diverse group of Borrelia bissettii strains and a homogenous group of Borrelia burgdorferi sensu stricto strains, a group of 16 isolates with unusual characteristics was found. The isolates were cultured from ear biopsy samples of the rodents Peromyscus gossypinus and Neotoma floridana trapped at five localities in South Carolina. A multilocus sequence analysis of the rrf-rrl intergenic spacer, 16S rRNA, fla, ospA, and p66 genes were used to clarify the taxonomic status of the new group of B. burgdorferi sensu lato isolates. Thirteen species of the B. burgdorferi sensu lato complex were used as controls. Unique restriction fragment length polymorphism patterns of the rrf-rrl intergenic spacer region and fla gene were recognized. Unique signature nucleotides were also found in the 16S rRNA gene. A phylogenetic analysis shows that the 16 new isolates cluster together but separately from the other species in the B. burgdorferi sensu lato complex. Our data strongly support the recognition of the 16 isolates as a new B. burgdorferi sensu lato species. We propose to name this genospecies "Borrelia carolinensis" with respect to the place of its currently known geographic location.
Keywords: bakteriální RNA; Borrelia burgdorferi komplex; Sequence Homology, Nucleic Acid; Cluster Analysis; Bacterial Proteins; fylogeneze; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Phylogeny; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; shluková analýza; sekvenční homologie nukleových kyselin; Sigmodontinae; Borrelia burgdorferi Group; mezerníky ribozomální DNA; Southeastern United States; geny rRNA; DNA, Bacterial; DNA bakterií; jihovýchod USA; Animals; Genes, rRNA; zvířata; křeček rodu Peromyscus; Peromyscus; bakteriální proteiny; RNA ribozomální 16S; DNA, Ribosomal Spacer; Molecular Sequence Data; DNA, Ribosomal; RNA, Bacterial